1998
DOI: 10.1116/1.581386
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous reactions of NO2 on NaCl and Al2O3 particles

Abstract: In this study, heterogeneous reactions of NO2 on NaCl and Al2O3 particles, two different types of particles present in the Earth’s atmosphere, are compared. Transmission Fourier-transform infrared spectroscopy and diffuse reflectance UV/Vis spectroscopy are used to characterize gas-phase and adsorbed products following reaction with NO2. For Al2O3 particles, two adsorbed species have been identified. At low NO2 pressures, adsorbed nitrite is formed whereas at higher NO2 pressures, nitrate is present on the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
67
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 25 publications
12
67
0
1
Order By: Relevance
“…2a and reported in previous studies. 3,[12][13][14]17,[56][57][58] The formation of additional products with peaks at 1280, 1584, and 1609 cm À1 when the C8= SAM is present, accompanied by a decrease in the -CH 2 -and QCH peaks (Fig. 2b), indicate that some of the surface-bound products of the NO 2 chemistry react with the attached organic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2a and reported in previous studies. 3,[12][13][14]17,[56][57][58] The formation of additional products with peaks at 1280, 1584, and 1609 cm À1 when the C8= SAM is present, accompanied by a decrease in the -CH 2 -and QCH peaks (Fig. 2b), indicate that some of the surface-bound products of the NO 2 chemistry react with the attached organic.…”
Section: Discussionmentioning
confidence: 99%
“…While there have been a number of studies of the uptake and reactions of NO 2 on alumina both in the absence and presence of water, 3,[12][13][14][15]17,18,[56][57][58][59]63 we are unaware of any study in which a SAM-derivatized alumina substrate was exposed to NO 2 . Although perfectly ordered SAMs may provide an effective barrier between the gas-phase and the substrate, previous studies have shown that gases may penetrate between the hydrocarbon chains, 64,65 especially at the edges of defects and islands of a rough substrate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…221 The components of dust particles include not only silicates, but also a number of other components such as Fe 2 O 3 , Al 2 O 3 , and TiO 2 . 8 Nitric oxide has been reported as the major gas phase product from the heterogeneous reaction of NO 2 on these surfaces in the absence of water vapor by Grassian and coworkers; [204][205][206][207][208] HONO may be a major gaseous product when there are significant amounts of water on the surface. Bö rensen et al 209 reported the formation and subsequent loss of nitrite ions on the surface of Al 2 O 3 during its reaction with NO 2 in the absence of water vapor and proposed that the loss was due to acidification of the surface that converts surface nitrite to gas phase HONO.…”
Section: B Airborne Particles and Cloudsmentioning
confidence: 99%
“…A UV-vis spectrophotometer (PE Lambda 20) equipped with an internal diffuse reflectance attachment (LabSphere) was used to measure %R, %R = R/Ro x 100, where Ro is the reflectivity of the mineral oxide prior to reaction and R is the reflectivity after reaction with NO 2. The sample holder has been described previously (Goodman et al, 1998).…”
Section: Introductionmentioning
confidence: 99%